EXTENSIVE SPINAL EPIDURAL ABSCESS - Riaz, Salman; Mahmood, James K. (Journal of Ayub Medical College Abbottabad, 2007)
Spinal epidural abscess (SEA) is a rare clinical entity associated with a high morbidity and mortality. It usually spans 3-4 levels. The literature contains very few reports of extensive or panspinal epidural abscesses and hence there is no consensus on management of such cases. We describe a case of 56 years old male presenting with a posteriorly located SEA extending from the Foramen Magnum to thoracolumbar junction. The abscess had led to quadriparesis for the last 24 hours. This abscess was treated operatively by performing noncontiguous minimally invasive decompressions of the cervical and thoracic spine. The patient showed progressive improvement in neurologic status and was walking with minimal support at 4 months of follow-up. Keywords: Epidural; Abscess; Paralysis; Thoracic; Laminectomy; Ambulation.